Pengembangan Sistem Keamanan Portal Otomatis Cerdas melalui Identifikasi Pelat Nomor Kendaraan Berbasis OCR di Satrad 232 - Hafid, Alif Riskiyadi; Dewanto, Yohannes (Universitas Dirgantara Marsekal Suryadarma, 2025)
The motorcycle parking system at Universitas Dirgantara Marsekal Suryadarma still operates manually without access control, vehicle recording, or integrated security mechanisms. This condition leads to congestion during peak hours, a high risk of vehicle theft, and low management efficiency. This study aims to design and evaluate a prototype of an automated parking gate system utilizing an Arduino-based microcontroller, RFID technology for vehicle identification, and ultrasonic/Vehicle Loop Detector (VLD) sensors for vehicle presence detection. A Research and Development (R&D) method was employed, involving field observation, technical measurements, and functional as well as performance testing of the system. The experimental results show that the system successfully validates registered RFID cards with a response time of less than 1 second, detects vehicles through the VLD sensor in less than 0.5 seconds, and opens the automatic barrier gate with an average speed of 2.30 seconds, meeting the device specifications. The safety auto-reverse feature also operated effectively with a reaction time of less than 1 second upon detecting obstacles during gate movement. All functional test scenarios achieved a 100% success rate in vehicle detection, access validation, and automated gate operation. This study demonstrates that integrating RFID and ultrasonic-based detection into a campus-scale parking system significantly enhances security, accelerates access processes, and provides a foundation for real-time vehicle data recording. The developed prototype can serve as a reference model for implementing a more efficient and secure smart-campus parking system.